Cardiovascular risk and obesity - Bryce Moncloa, Alfonso (2017)
Obesity is a chronic multifactorial disease that has reached global epidemic proportions, representing a complex medical condition with serious social and psychological consequences. The excess of visceral adiposity is associated with a plethora of metabolic dysfunctions (insulin resistance, atherogenic dyslipidemia, hypertension, decreased fibrinolysis, increased risk of thrombosis, endothelial inflammation) that increase the risk of cardiovascular disease. The strategies proposed for the correct therapeutic approach must be in accordance with the severity of overweight, the presence of chronic coexisting diseases and the functional limitations of each individual.